Effects of maternal dietary heme Fe supplementation on liver iron levels and expression of iron regulatory genes in newborn piglets - Li, Meiquan; Zhao, Meiwei; Zhang, Chunyong; Ji, Qiaoping; Wang, Xiao; Du, Yanli; Chen, Kelin; Ji, Fuqing; Huang, Shuting; Guo, Rongfu (Frontiers in Animal Science, 2025)
Iron deficiency in sows has been demonstrated to have a detrimental effect on porcine fetal growth and development, as well as on the reproductive performance of sows. The placental barrier of sows restricts the transportation of inorganic iron to the fetus, resulting in iron deficiency anemia in neonatal piglets and consequently leading to slow growth. The purpose of this study is to explore the effect of heme Fe on iron metabolism in pregnant sows. Ninety-six multiparous Landrace × Yorkshire (LY) sows (weight 235 ± 15kg) with similar litter size and feeding management were randomly divided into four treatment groups: control group (supplemented with 400 mg/kg), iron deficiency group (with no added FeSO4), heme Fe group (supplemented with 140 mg/kg), and glycine Fe group (supplemented with 470 mg/kg). Iron supplementation lasted from the second trimester (day 30) to day 114 before delivery. In this study, the production performance of sows, the iron content in sow placentas, and in the livers, spleens, placenta and colostrum of newborn piglets, as well as the hemoglobin(HGB) level, the iron regulation parameters in the serum of newborn piglets and the iron regulation genes in the livers and placentas were measured. The results showed that: (1) The number of live births and the average birth weight of piglets in the heme Fe group were 14.8% and 6.33% higher than those in the control group, respectively(P < 0.01). Compared with FeSO4 and glycine Fe, heme Fe improved the production performance of sows. (2) In the heme Fe group, the iron content in colostrum was significantly higher than in the control group (1.27-fold) and glycine Fe group (0.45-fold), while the iron content in the livers of newborn piglets increased by 30.38% and 14.61% compared to the control and glycine Fe groups, respectively (P < 0.01). These results suggest that heme Fe significantly facilitates iron transport in sows, particularly enhancing its deposition in colostrum and neonatal livers. This effect may be attributed to the upregulated expression of heme oxygenase 1(HO-1) gene in the placenta, which enhances the uptake and transport of heme Fe, thereby increasing fetal iron acquisition.(3) In the liver and placentas of sows in the deficiency group, the expression of hepcidin was decreased, while the expressions of transferrin receptor 1 (tfr1), feline leukemia virus subgroup C receptor 1(Flvcr1) and transferrin were increased (P < 0.01). In addition, the gene expression level of HO-1 in the heme Fe group of liver was significantly higher compared to that in the control group (1.85-fold), the iron deficiency group (2.99-fold), and the iron glycinate group (1.67-fold). In conclusion, maternal heme Fe supplements have a significant impact on iron storage in neonatal piglets and are helpful for preventing iron deficiency in newborn piglets.